The Effect of Workload and Perception of Organizational Support on Job Satisfaction with Work-Life Balance as A Mediating Variable in the Shared Services Function of Pt Pertamina (PERSERO) - Fahmi, Irfan; Riyanto, Setyo (Archives of Business Research, 2024)
The aim of this research is to determine how workload and the perception of organizational support impact job satisfaction, as well as how work-life balance acts as a mediating variable in the Shared Services Function of PT Pertamina (Persero). The research strategy employed by the author is quantitative in character, as it is grounded in concrete, objective, quantifiable, logical, and methodical data. Because it contains samples from every permanent employee of PT Pertamina (Persero) as well as from the whole population of the Shared Services Function, the study's sample is known as a saturated sample, or full population. 321 individuals make up the entire population sample. Structural Equation Modelling (SEM) is a data analysis methodology that was employed in this work to solve the limitations of the regression method. The Partial Least Square (PLS) software application is used in this study's analysis to process the data. Variant Based Structural Equation Modelling is then used to test the hypothesis and provide a viable model. The results showed that workload had a negative and significant impact on job satisfaction in the SS Function of PT. Pertamina (Persero). Job satisfaction with SS Function PT. Pertamina (Persero) is positively and significantly impacted by employee perceptions of organizational support. In SS PT Function Pertamina (Persero), work-life balance is adversely and significantly affected by workload. The perception of organizational support has a favorable and considerable impact on work-life balance, as per the SS function of PT. Pertamina (Persero). Work-life balance and job satisfaction have a somewhat positive association in SS Function PT. Pertamina (Persero). Work-life balance makes it possible for employee happiness at PT. Pertamina (Persero), an SS function, to be indirectly impacted by workload. The SS function PT. Pertamina (Persero) believes that work-life balance has an indirect effect on satisfaction through organizational support.